Specialist versus Generalist at the Intraspecific Level: Functional Morphology and Substrate Preference of Mediodactylus kotschyi Geckos. (28th June 2021) - Schwarz, Rachel; Stark, Gavin; Antonopolous, Antonis; Itescu, Yuval; Pafilis, Panayiotis; Chapple, David G; Meiri, Shai
Synopsis: Populations of the same species occupying different microhabitats can either exhibit generalized traits across them or display intraspecific variability, adapting to each microhabitat in order to maximize performance. Intraspecific variability contributes to the generation of diversity, following selection and adaptation, and understanding such variability is important for comprehending how individuals choose their microhabitats. Compared with interspecific variability, however, intraspecific variability in functional morphology and its relationship with microhabitat preference and use have been relatively little studied. Here we examined whether populations of the gecko Mediodactylus kotschyi that differ in the substrates they occupy display habitat-specific behaviors and differing morphologies associated with functional adaptation to their microhabitats. We collected 207 geckos from under or on rocks or on trees from seven populations in Greece. On large islands individuals occupy both substrates; whereas small islets are devoid of trees and the geckos are restricted to rocks, while on the mainland they are only found on trees. We determined gecko substrate preferences in the laboratory, together with their clinging abilities to the different substrates. We measured their limbs, digits, and claws and assessed how these measurements relate to clinging ability. Geckos from all populations preferred the tree made available to them, but this preference was not statistically significant. Geckos from both large and small islands clung better to the tree than to the rock in the laboratory, while those from the mainland clung similarly to both substrates. Geckos collected from trees had longer manual digits and hind limbs. Geckos collected from large and small islands had taller (longer on the dorso-ventral axis; henceforth "deeper") claws. Longer digits and deeper but shorter claws were associated with a better ability to cling to rocks. Our findings suggest that while M. kotschyi is potentially preferentially arboreal, due to the great variation and plasticity it possesses, it can successfully also exploit the habitats available on the smallest, treeless islets in the Aegean Sea. Our study suggests that the dichotomous use of generalist versus specialist in describing species' habitat use is oversimplified, and we suggest the use of a generalist–specialist gradient instead.